Improving productivity through lean and SLP implementation: a case study of a metalworking company in Peru - Iglesias Rivera, Luis Diego (2025)
The main objective of this research is to develop a model to increase productivity in a metal-mechanical company in Peru, through the implementation of plant layout tools, such as SLP, and Lean tools, such as 5S and SMED. It is important to highlight that, in 2023, the metal-mechanic industry represented 1.5% of the national Gross Domestic Product (GDP), contributing with a value of 567,390 million soles, equivalent to 151,860 million U.S. dollars. The problem identified is in the workshop area, where cable trays are manufactured, and where productivity is 0.1831 finished products per man-hour. This corresponds to a production order of 200 linear meters of finished product. The solution model was based on the Lean methodology, applying the 5S and SMED tools in order to reduce the time of non-productive activities, such as area cleaning, selection of tools and materials, and equipment readiness. In addition, the SLP tool was used for plant redistribution, with the objective of proposing a new layout for the workshop area, including a raw material warehouse and a finished product warehouse. The results obtained from the simulation of the proposed model with Arena software showed that, by implementing a plant redistribution with two warehouses (one for raw material and one for finished product), and reducing the activity times, productivity increased to 0.2168 trays produced per man-hour, with a simulated production time of 12.14 days.